2019
DOI: 10.1002/jsde.12252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Nanoparticles on Wormlike Micelles with Different Entanglement Degrees

Abstract: Enhancing the viscoelastic properties of wormlike micelles by adding nanoparticles has been widely reported. Various mechanisms have been proposed to explain how nanoparticles strengthen the network formed by wormlike micelles. It remains unclear whether nanoparticles produce the same effect on systems with different entanglement degrees. To clarify this issue, the concentration of potassium chloride was used to control the entanglement degree of wormlike micelles. The rheological behavior of different nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…The transport of proppant depends on the viscosity characteristics of the system in this case. At high oscillation frequency, the storage modulus G′ is greater than the loss modulus G″, and the system exhibits solid phase properties, and the transport of proppant depends on the elastic characteristics of the system (Rehage and Hoffmann, 1988;Zhao et al, 2019). When the oscillation frequency is 1.60 Hz, the system storage modulus G′ is equal to the loss modulus G″, and the reciprocal of the oscillation frequency is referred to as the relaxation time, which is 0.63 s. In addition, at higher oscillation frequencies, the storage modulus G′ is basically unchanged, while the loss modulus G″ decreases first and then increases again with the increase of frequency.…”
Section: Viscoelastic Performance Of Fracturing Fluid Systemmentioning
confidence: 99%
“…The transport of proppant depends on the viscosity characteristics of the system in this case. At high oscillation frequency, the storage modulus G′ is greater than the loss modulus G″, and the system exhibits solid phase properties, and the transport of proppant depends on the elastic characteristics of the system (Rehage and Hoffmann, 1988;Zhao et al, 2019). When the oscillation frequency is 1.60 Hz, the system storage modulus G′ is equal to the loss modulus G″, and the reciprocal of the oscillation frequency is referred to as the relaxation time, which is 0.63 s. In addition, at higher oscillation frequencies, the storage modulus G′ is basically unchanged, while the loss modulus G″ decreases first and then increases again with the increase of frequency.…”
Section: Viscoelastic Performance Of Fracturing Fluid Systemmentioning
confidence: 99%
“…The NPs can increase the zero-shear viscosity η 0 , relaxation time τ rel , and the plateau modulus G 0 of VES fluids ( Figure 2 ) [ 94 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. The most pronounced is the effect of NPs on the viscosity, which can augment by up to 3 orders of magnitude [ 94 , 96 , 98 , 99 , 100 , 104 , 105 , 106 , 107 , 108 , 110 , 111 ]. It can be attributed to the hindered reptation of WLMs as their motion slows down in the vicinity of NPs.…”
Section: Nanoparticle-enhanced Ves Fluidsmentioning
confidence: 99%
“…In some papers [ 94 , 105 , 107 , 111 ], it was observed that upon the gradual increase in the amount of added NPs (at a constant concentration of surfactant) the zero-shear viscosity first increases, reaches a maximum, and then starts to decline. For instance, in VES fluid composed of a C22-tailed cationic surfactant N-erucamidopropyl-N,N-dimethyl-N-allylammonium bromide (EDAA) and negatively charged SiO 2 particles, the maximum value of viscosity was observed at as low an amount of NPs as 0.01 wt %, and the further increase in the NP concentration resulted in the decrease in viscosity, which became even lower than the viscosity of the initial VES solution [ 94 ].…”
Section: Nanoparticle-enhanced Ves Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,21 Based on the concentration and ionic strength of components as well as molecular architecture, self-assembly of surfactants forms micelles of varying shapes such as spherical micelles, 22 rod-like micelles, 23 vesicles, 24 and wormlike micelles (WLM). 25,89 Because of the formation of entanglement, overlap and networks, long and exible WLM in an aqueous system exhibit excellent viscoelastic characteristics similar to the polymer solution but no residues. 26,27 Several researchers studied the clean fracturing uid with high ow back rate, low friction, and low damage to the formation with the surfactant system.…”
Section: Introductionmentioning
confidence: 99%